Konsumsi Konten: Memotivasi Penggunaan TikTok Live di Luar Fungsi Hiburan - Fahira Rizany; Ni Luh Yulyana Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine users’ motivations for utilizing TikTok Live beyond its entertainment function, focusing on the emerging dimensions of education and social interaction on the platform. The research employs a literature review method by analyzing national and international scientific journals published within the last five years, particularly those addressing social media user behavior and the dynamics of digital communication. The analysis reveals that TikTok Live has undergone a functional transformation from a mere entertainment tool to an interactive and collaborative learning medium. Users employ this live broadcasting feature not only for entertainment but also as a space for knowledge sharing, real-time discussion, and the expansion of interest-based social networks. The high level of interactivity provided by features such as comments, duets, and live chats makes TikTok Live an effective medium for creating participatory learning experiences. These findings emphasize that TikTok Live holds significant potential as an educational medium capable of influencing users’ content consumption behavior, enhancing digital literacy, and fostering social participation. Therefore, this study recommends further exploration of pedagogical aspects, algorithms for educational content distribution, and the social impacts of TikTok Live within the context of contemporary digital education.